6か月男児の下顎骨と体幹皮膚に生じた多臓器多病変型ランゲルハンス細胞組織球症の1例 - 渋谷, 恭之; 中村, 知寿; 森下, 雄斗; 鍋田, 剛志; 加藤, 伸一郎; 福島, 麻子 (日本口腔外科学会雑誌, 2020)
Langerhans cell histiocytosis (LCH) is a relatively rare proliferative disorder of Langerhans cells. We herein report an extremely rare case of LCH arising in the mandible and trunk skin of a 6-month-old boy. A patient was referred to our clinic because of right cheek swelling. Computed tomography revealed broad bone expansion and a defect in the right mandibular molar region. An excisional biopsy was performed, and the lesion was histopathologically diagnosed as LCH (multi-system multi-site: MM type). Immunohistochemically, the histiocytes were positive for S -100 and CD1a. The patient subsequently underwent chemotherapy (vinblastine and prednisolone), and the lesion was reduced completely. Long-term follow-up should be practiced to monitor for tumor recurrence and hypoplasia of the teeth as a side effect of chemotherapy. There has been no recurrence after 2 and a half years of follow-up.